Protection of modern power grids with multiple renewable sources and power converters - Li, Chao. (2010)
The most important concern of all power grids is their protection systems. Traditionally, they have been met by mechanical relays and circuit breakers. However, in modern grids, where multiple renewable sources and power electronic converters are widely used, new means of implementing grid protection has become possible.